Migraine and temporomandibular disorder triggered by stress-induced bruxism: a case report: Migrain dan gangguan temporomandibular yang dipicu oleh bruxism yang diinduksi stres: laporan kasus - Astari Larasati; Pinta Marito; Laura Susanti Himawan; Ira Tanti (Makassar Dental Journal, 2022)
Migraine is the most common primary headache that associated with temporomandibular disorders (TMD) that is known as number of clinical problemsinvolving the masticatory muscles, temporomandibular joint and associated structures. Bruxism may be considered as an important factor of initiation of TMDand stress might be the contributory factor. This article is aimed to discuss the management of migraine and TMD patient with stress-induced bruxism as aprecipitating factor. A 42-year-old male patient visited RSKGM FKGUI due to throbbing pain, headache and discomfort around ear and face. Patient was diag-nosed myalgia based on DC/TMD with no articular joint disorder and migraine according to orofacial pain classification axis-1 following with anxiety disorder and stress. A stabilization appliance was designed followed with patient education, physical therapy and stress management. It was concluded that treatment combination of stabilization appliance, stress management and significantly improve the patient’s condition with lessen migraine attack and TMD symptoms.